Assessment of Nutritional Status of Patients on the Maintenance Hemodialysis at Tertiary Care Hospital using Malnutrition Inflammatory Score - Tahir, Hasham Bin; Khan, Malik Nadeem Azam; Tariq, Rabia; Khan, Raheel; Ahmed, Bilal; Khan, Hafiz Waleed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of protein energy wasting among end stage renal disease patients on maintenance hemodialysis.Study Design: Cross-sectional analytical study.Place and Duration of Study: Department of Nephrology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from May 2019 to Mar 2020.Methodology: Two hundered patients diagnosed with end-stage renal disease on maintenance hemodialysis were included in the study. Protein-energy wasting was assessed using the Malnutrition inflammatory score comprising four x components: medical history, physical examination, laboratory parameters and body mass index. Malnutrition inflammatory score was used to categorize protein-energy wasting.Results: Out of 200 patients with ESRD on maintenance hemodialysis, 73(36.5%) patients had mild, 120(60.0 %) patients had moderate, and 7(3.5%) patients had severe protein-energy wasting. The advanced age group, multiple comorbid (diabetes mellitus, hypertension, ischemic heart disease), and duration of hemodialysis (> 2 years) had a statistically significant association with the protein energy wasting (p-value < 0.05). Protein-energy wasting was also more prevalent in patients with low monthly income (p-value 0.04).Conclusion: Protein-energy wasting is common among patients with end stage renal disease on maintenance hemodialysis.Old age group, multiple comorbid, and duration of hemodialysis are important risk factors.